Implementation and Constraints of Diagnostic Assessment in the Independent Curriculum Towards Deep Learning-Based Biology Learning in High Schools - Haka, Nukhbatul Bidayati; Masya, Hardiyansyah; Rakhmawati, Ismi; Puspita, Laila; Jamaludin, Didi Nur; Oktafiani, Raicha (Wise Education, 2025)
The implementation of diagnostic assessments in the Independent Curriculum is a crucial step in mapping students' initial abilities and designing appropriate learning strategies. This study aims to identify obstacles to the implementation of diagnostic assessments in deep learning-based biology learning in public senior high schools in Bandar Lampung City, encompassing the planning, implementation, and follow-up stages. The study used a descriptive qualitative approach with a purposive sampling technique. The sample consisted of three public senior high schools, four biology teachers, and 69 tenth-grade students studying Biodiversity. Data were obtained through interviews, observations, questionnaires, and documentation. Data were analyzed through data reduction, data presentation, and conclusion drawing. The results showed that the implementation of diagnostic assessments was not optimal. Only two schools had implemented cognitive and non-cognitive diagnostic assessments, while one school had not implemented them at all. The main obstacles lay in limited school facilities and the low level of socialization regarding the Independent Curriculum, particularly the implementation of diagnostic assessments in innovative, deep learning-oriented biology learning. However, limited understanding and institutional support remained a significant obstacle. This study recommends improving teacher training, providing supporting facilities, and implementing more systematic assessment follow-up policies